Biopreservative effect of bacteriocin in fruit juice preservation - Ali, Mohammad Shaokat; Begum, Ayesha; Uddin, Md Forhad; Ahmed, Shamima (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This study aimed to evaluate the biopreservation activity of bacteriocin against some spoilage organisms. This bacteriocin was produced by lactic acid bacteria (LAB) isolated from dahi samples. Man Rogosa Sharpe (MRS) broth and agar were used for the isolation of LAB from the dahi. Bacteriocins are antibacterial proteins produced by bacteria that kill or inhibit the growth of other pathogenic and spoilage bacteria. Many lactic acid bacteria produce a high diversity of different bacteriocins. This study was conducted to produce the bacteriocin which produced by Lactobacillus spp. from dahi sample. Dahi samples were collected from different retailer shops of Chittagong Metropolitan Area (CMA). Lactobacillus spp. was isolated from these dahi samples by using MRS broth (Hi-Media, India) at 37ºC for 48 h. The crude bacteriocin was produced and purified by ammonium sulphate precipitation. The adversary properties of bacteriocin were perused by agar well diffusion method. The durability of bacteriocin was studied in different temperature and pH. The bacteriocin was stable at 37ºC and acidic pH. The antimicrobial activity of the isolates was done by growth inhibition test against some selected pathogenic microorganisms likely Escherichia coli, Pseudomonas aeroginosa, Salmonella paratyphi. The result showed that the isolates of Lactobacillus spp. inhibited the growth of these pathogenic organisms. By this study the antibacterial efficacy of bacteriocin was determined for fresh orange juice. The biopreservative effect of bacteriocin was observed on the basis of low colony counts in total plate count agar (TPA). The study result showed that bacteriocin producing Lactobacillus spp. can be successfully used as biopreservative for fruit juice preservation. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 435-440